Parliamentary oversight of government acts - García Barzelatto, Ana María (Revista de Derecho Público, 2015)
It studies the exclusive power of the Chamber of Deputies to audit government acts, including the historical-normative evolution of auditing with special reference to the constitutional reform of 2005, which established three auditing modalities. It examines the scope of the expressions "request background information" and "government acts" in order to determine the extension that corresponds to the supervision of the Chamber of Deputies.